Evaluating beauveria bassiana fungal growth in packed bioreactor (2003)
The efficiency of a packed bioreactor for growing Beauveria bassiana was evaluated by using a solid substrate consist-ing of whole wheat as growth source. Temperature and fungal growth were analysed. The parameters used for evaluating the bioreactor were layer thickness, airflow and position inside the bioreactor. Operation time was pre-determined; it was used to study fungal growth parameters and productivity. Using Tukey test and a factorial experimental design such as H/D = 0.9 (H: layer height, D: bioreactor diameter) and 12.3 L/min airflow operating conditions, it was observed that fungal productivity was significantly increased compared with the traditional bottle method on the scale being evaluated. Position was the least significant of those factors studied for improving fungal growth. Key words: solid-state fermentation, biological control